(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
Tambrauw as one of the regencies in West Papua, is well known as a megabiodiversity area, including marine microalgae that have an important role in the food chain system in the water. On the other hand the diversity of marine microalgae in this area has not been studied much. This study was conducted to identify marine microalgae from Tambrauw based on morphology and molecular approach. Marine microalgae were isolated from natural sources in Tambrauw, purified and cultivated under standard conditions. Fourteen cultures of marine microalgae were selected based on growth, diversity of morphology and homogeneity. The morphological characteristics were observed using light microscopy and the phylogenetic relationships of each strain were defined according to the 18S rRNA sequence analysis in the eukaryotic group and 16S rRNA in the prokaryotic microalgae group. The resultant sequences were compared with those available on the NCBI website database through the BLAST bioinformatic tool. The results showed high similarity with known nucleotide sequence identified as Monoraphidium neglectum (99%), Chlorella sorokiniana (99%), Oocystis heteromucosa (99%), Ettlia texensis (99%), Dilabifilum arthopyreniae (98%), Auxenochlorella protothecoides (99%), Trichosarcina polymorpha (98%), Scenedesmus vacuolatus (99%), Chlorella kessleri (99%), Coelastrella oocystiformis (99%), dan Foliisarcina bertiogensis (99%). This study is the basic information in revealing the diversity patterns of microalgae, which are very important to obtain new genetic resources for industrial purposes as well as for taxonomic studies.